Uji Laboratorium Sampel Core Plug untuk Menentukan Porositas, Permeabilitas dan Saturasi Minyak pada Reservoir Batugamping - Arief Rahman; Rani Rahmawati (Jurnal Indonesia Sosial Teknologi, 2022)
Porosity, permeability, and fluid saturation (gas, oil, water) are three important physical properties of rocks, especially in oil and gas reservoirs (oil and gas) which are carried out in core rock analysis. The purpose of this study is to determine the relationship between porosity, permeability, and oil saturation in limestone (limestone) from a horizontal plug core sample to a vertical core plug sample, to be associated with its distribution vertically and horizontally (laterally). The research method used is a Lab Test conducted at the Routine Core Analysis (RCAL) Laboratory at PPTMBG "Lemigas" Jakarta, and graphical analysis of the measurement results. The core plug samples used were 21 (twenty one) which were taken horizontally and 10 were taken vertically, which has been described, from conventional core samples from limestone reservoirs. The results of his research are that the porosity values ​​of the vertical and horizontal samples of limestone have an indistinguishable trend, while limestones without chalky have a deeper trend, the porosity is greater, while porosity with chalky has a scatter trend, this indicates that the porosity of limestones is higher. influenced by lithological conditions or depending on the facies and the time of diagenesis, not depending on the depth (as in the case of sandstone). The value of oil saturation in the vertical and horizontal samples has a distribution that can be said to not show a certain trend or scatter. The relationship between porosity and permeability is exponentially proportional, regardless of depth and vertical or horizontal core sampling position. The value of porosity and permeability of limestone with the presence of chalky is more dominant, significantly increasing the value of porosity and permeability compared to that without the presence of chalky.